SISTEM IDENTIFIKASI SIDIK JARI DARI CITRA HASIL SCANNING MANUAL MENGGUNAKAN METODE EKSTRAKSI DAN PENCOCOKAN CITRA BERBASIS MINUTIAE, EUCLIDEAN DISTANCE, DAN ALGORITMA PEMBATAS ADAPTIF - , RESTU AJI PRAMANA P; , Drs. Panggih Basuki, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fingerprints are part of the body which has distinctive characteristics whereby one person to another is not the same, even if they are identical twins. On the basis of these circumstances, it develops a connection with the invention of the biometric system which is nothing but the goal is to determine the characteristics or characterization of fingerprints from every person. So the knowing the fingerprint characteristics, would be useful for a more specific purpose, such as identifying and verifying fingerprints. The fingerprint identification system will be the topic of the study authors, therefore made fingerprint identification systems, from image of the manual scanning result using image extraction and matching methods based on minutiae, euclidean distance, and adaptive boundary algorithm, designed to analyze whether the fingerprint image obtained can produce characteristic information which can be used for identifying and recognizing the fingerprint. The processing and matching of image from 150 images test and 80 images training, obtained recognition rate percentage at 93.33%.